2019
DOI: 10.3390/nu11122856
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Structural Individual Low-FODMAP Dietary Advice vs. Brief Advice on a Commonly Recommended Diet on IBS Symptoms and Intestinal Gas Production

Abstract: A low fermentable oligosaccharide, disaccharide, monosaccharide, and polyol (FODMAP) diet has been recommended for irritable bowel syndrome (IBS) patients. This study compared the efficacy of two types of dietary advice: (1) brief advice on a commonly recommended diet (BRD), and (2) structural individual low-FODMAP dietary advice (SILFD). Patients with moderate-to-severe IBS were randomized to BRD or SILFD groups. Gastrointestinal symptoms, 7-day food diaries, and post-prandial breath samples were evaluated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 21 publications
(30 reference statements)
2
56
0
Order By: Relevance
“…We can explain this result because patients with IBS usually have a surrounding visceral hypersensitivity and are more susceptible to bowel distension. Low FODMAPs diet reduces the amount of bowel gas, as demonstrated by Patcharatrakul T et al and this, in turn, could be the reason of our observation [37]. They demonstrated a difference in H2 and CH4 breath concentrations, before and after low FODMAPs diet.…”
Section: Discussionsupporting
confidence: 78%
“…We can explain this result because patients with IBS usually have a surrounding visceral hypersensitivity and are more susceptible to bowel distension. Low FODMAPs diet reduces the amount of bowel gas, as demonstrated by Patcharatrakul T et al and this, in turn, could be the reason of our observation [37]. They demonstrated a difference in H2 and CH4 breath concentrations, before and after low FODMAPs diet.…”
Section: Discussionsupporting
confidence: 78%
“…This situation makes it challenging to evaluate the effect of a low-FODMAP diet effect on Asian patients with IBS. In this issue, the effect of a low-FODMAP diet in Thai IBS patients is compared to the commonly recommended diet, which is a variant of National Institute for Health and Care Excellence-modified diet (NICE-modified diet) [4]. It was found that 60% of the Thai IBS patients responded to a low-FODMAP diet, which is similar to reports that 50-72% of western IBS patients respond to a low-FODMAP diet [5][6][7].…”
Section: Role Of Diet In the Management Of Ibssupporting
confidence: 59%
“…The low FODMAP diet also led to greater reductions in bloating, urgency, and stool frequency 41 . Similarly, another RCT showed higher response rates in the low FODMAP group (60%) compared to first‐line IBS diet (28%, P = .001), as well as lower total IBS‐SSS scores 42 …”
Section: Whole Dietsmentioning
confidence: 85%